A Group Counselling Using the Reframing Technique to Improve Academic Self-Awareness of High School Students - Bakhrudin All Habsy; Titin Indah Pratiwi; Tri Desi Wulandari (Indonesia Approach Education, 2024)
Academic self-awareness in learning is the awareness of students at schools to adjust, understand and control themselves according to the rules that apply at schools. Not only learning and increasing knowledge, but students must also be able to control themselves well according to expectations and purpose. This type of research is Quasi-Experimental Design research with a Pre-test Post-test Control Group Design research model. The population in this study was class XI Senior High School. The research sample consisted of 10 people divided into an experimental group and a control group of 5, each. Data was collected through an academic self-awareness questionnaire developed by researchers with 49 items based on aspects of emotional awareness, accurate self-assessment, and self-confidence. This study aims to measure the effect of the treatment given on the dependent variable (bound). Data processing and data analysis techniques are using Statistical Product and Service Solution (SPSS) version 21. Based on the results of statistical data analysis of the paired sample t-test, asymp. Sig (2-tailed) of 0.002 result was obtained. Because the value of asymp. Sig (2-tailed) is less than 0.05, then H1 is accepted, and Ho is rejected, therefore, a group counselling is an effective reframing technique to increase academic self-awareness of students.